The last kids on earth and the cosmic beyond eaudiobook - Brallier, Max (Last Kids on Earth, 2018)
A Netflix Original series!  The fourth book in the New York Times, USA Today, and Wall Street Journal bestselling series, with over 7 million copies in print! "Terrifyingly fun! Delivers big thrills and even bigger laughs."— Jeff Kinney, author of the #1 New York Times bestseller Diary of a Wimpy Kid It's the first winter after the monster apocalypse. For Jack and his buddies, that means sled catapults, epic snowball battles, and one monstrous Christmas celebration. But their winter wonderland turns dark when a villainess begins hunting them. And this villainess is different—she’s a human.   When the villainess steals Jack's prized monster-slaying tool, the Louisville Slicer, he vows to get it back. But it won’t be easy. Jack and his friends soon discover that the Louisville Slicer is the key to a dark plan that threatens the entire world—and beyond... Told in a mixture of text and black-and-white illustration, this is the perfect series for any kid who's ever dreamed of starring in their own comic book or video game.